Decreased Functional Connectivity of Vermis-Ventral Prefrontal Cortex in Bipolar Disorder - Li, Huanhuan; Liu, Hu; Tang, Yanqing; Yan, Rongkai; Jiang, Xiaowei; Fan, Guoguang; Sun, Wenge (Frontiers in Human Neuroscience, 2021)
Objectives: To investigate the changes of functional connectivity between vermis and cerebral regions in resting state in Bipolar disorder (BD). Methods: Thirty participants with BD and 28 healthy controls (HC) underwent resting-state functional magnetic resonance imaging (fMRI). Resting-state functional connectivity (rsFC) of the vermis divided into anterior and posterior vermis was examined. For each participant, rsFC maps of the anterior and posterior vermis were computed and compared across the two groups. Results: Compared to the HC group, we found significant decreases in rsFC between the whole vermis and ventral prefrontal cortex (VPFC) in the BD groups, whereas rsFC between the anterior vermis and the middle cingulate cortex was significantly decreased in the BD group. Limitations: 83.3% of the BD participants were taking medication at the time of the study. We did not examine the effects of medication on rsFC in this study. Hence, our findings may in part be attributed to treatment differences; the mixed BD subtypes in our current study may have confounding effects on the results. Conclusions: These results strongly suggest that these rsFC differences of vermis-VPFC between groups may play a key role in the regulation of mood in BD.